Gay penguins, sissy ducklings … and beyond? Exploring gender and sexuality diversity through children's literature. Issue 6 (1st November 2016) - DePalma, Renée
ABSTRACT: From 2006 to 2008 UK-based primary school teachers in the No Outsiders project explored possibilities for addressing sexualities equality in their classrooms. What all teachers had in common was a resource pack that included 27 children's books exploring themes of gender and sexuality diversity either directly or indirectly (i.e. by the presence of same-sex parents or gender non-normative characters). While such books have the potential to productively trouble the heteronormative spaces of schools by the mere presence of characters who do not conform to sex/gender/sexuality expectations, some of them have also been criticized for reproducing heteronormative family structures and implicit values and failing to go beyond 'vanilla strategies' that feel safe in primary school settings. The experiences and reflections of the No Outsiders project members can help educators plan not only which kinds of literature to use but also how to incorporate such texts into the curriculum.